TECHNOLOGICAL STEWARDSHIP: ADVANCING ORGANIZATIONAL COMMUNICATION THROUGH IT GOVERNANCE - Harjono Padmono Putro (Jurnal Scientia, 2023)
Organizations need to develop innovative IT governance strategies to achieve more effective and sustainable communications. However, challenges continue to arise in optimizing the role of IT in the context of organizational communications. This research aims to investigate how the concept of technological stewardship can be key in advancing organizational communication through the implementation of sophisticated IT governance. This research uses a qualitative approach with descriptive methods. The results of this research confirm that Technological Stewardship and Information Technology (IT) governance play a central role in improving organizational communication. With good IT governance, organizations can create an efficient technology infrastructure, enabling rapid exchange of information and reducing technical barriers. The choice and implementation of the right communications platform through IT governance supports better collaboration between organizational members, while strict information security policies create a secure environment for sharing sensitive data. An integrated IT infrastructure also has a positive impact on the speed and accuracy of information delivery, preventing communication errors. Meanwhile, IT governance adaptability supports responsiveness to technological change, keeping organizations relevant in a rapidly changing business environment.